(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
Over more than three decades, intense research work has been carried out on Thermal Barrier Coatings (TBC). A variety of composite materials and deposition techniques have been developed. Presently, nanostructured TBCs have proved to be promising to deliver the desired properties and has become the driving force of TBCs research and development across the globe. Accordingly, great importance is associated with the wide range of deposition or processes techniques needed for development of nanostructured TBCs. From literature and articles, it has been observed that the enhancement in performances of mechanical, thermal and physical properties depends on the material and deposition technique used. In this paper, a review about Thermal Barrier Coatings and different types of deposition techniques involved for applying coatings and their investigative outcomes is presented.